PELATIHAN PENELITIAN SURVEI DALAM PEMBELAJARAN SEJARAH BAGI GURU SEJARAH SMAN 1 YOGYAKARTA - Fahruddin, Fahruddin (Jurnal Berdaya Mandiri, 2020)
This community service program is to provide survey research training to the history teachers at SMAN 1 Yogyakarta. It focuses on the enhancement of history learning and is conducted in three meetings. It firstly focuses on the importance of conducting survey research to see whether history learning is successful or not. It then presents the survey research methodology in history learning.  It lastly deals with survey research data processing and the application of Statistical Product and Service Solutions (SPSS).  The history teachers of SMAN 1 Yogyakarta are expected to have a better understanding of applying the survey research in history learning. It is also to familiarise the use of SPSS application for the survey research data processing. Besides, it is expected to raise teachers? enthusiasm for applying the survey research in their classroom activities learning.